Studi on the in vitro release of ibuprofen from xanthan gum matrix combined with a crosslinking agent - Hadisoewignyo, Lannie; Fudholi, Achmad (Indonesian Journal of Pharmacy, 2007)
Ibuprofen is non-steroidal anti-inflammatory drugs that is often used so frequently in a day that is can cause the patient to forget to take it. Besides it may cause gastro intestinal disturbances, which increase with the frequent of use. Many studies have been undertaken to obtain ibuprofen controlled release systems. Based on this, this study is done to find out the in vitro release kinetic of ibuprofen from xanthan gum matrix combined with a crosslinking agent, that is locust bean gum or calcium sulphate.In this research there were six formulas sustained release ibuprofen tablet that was made by the same compression pressure. Formula I, II and III used matrix combination of xanthan gum and locust bean gum (1:½, 1:1, 1:1½), while formula IV, V and VI used matrix combination of xanthan gum and calcium sulphate (1:½, 1:1, 1:1½). Afterward, the physical and release characteristics of the tablet were examined.The results showed that the compactibility of matrix combination of xanthan gum and locust bean gum was different from the matrix combination of xanthan gum and calcium sulphate. Combination of xanthan gum and locust bean gum and also calcium sulphate as crosslinking agent can influence the physical properties and the release profile of tablet.Key words: ibuprofen, xanthan gum, locust bean gum, calcium sulphate, dissolution, sustained release tablet.